Influences of motivation, perceived value of the Yang Knorr tourists on their satisfaction and behavior intention - Li, Hanliang; Zhou, Lingqiang; Zheng, Yibo (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2018)
Rural tourism and leisure vacation have become critical components of tourism development strategy of China. With the fast development and outstanding performance in tourism industry,"Yang Knorr", which usually refers to small inns located in the rural area with elegant architecture, simple design and comfortable facilities, features both rural tourism and leisure vacation. There is an urgent need to gain comprehensive understanding of the success factors for future development of Yang Knorr. This study takes tourists' feeling as the key of the success of Yang Knorr, aiming to investigate the relationship between tourists' motivation, perceived value, satisfaction, and behavioral intention. Based on the empirical analysis of 497 tourists' samples collected from 10 Yang Knorr, our results show that escaping from the constraints of human relationships, perceived functional value, showing-off, extended self, and uniqueness have significant influence on behavioral intention, and satisfaction is proved to be a med